Development of Powerpoint Interactive Learning Media in Package C Program in SKB City of Palembang - Faridha Banneti Istopiah; Yanti Karmila Nengsih (Universitas Negeri Padang, 2023)
In a teaching and learning process, learning media is one of the most crucial elements, because it can be applied to the material that will be delivered to students, both in the form of tools and teaching materials. One of the learning media that can increase the interest and interest of students is by using Powerpoint media which is packaged interactively. The purpose of this study was to develop interactive Powerpoint media with a valid application to the Package C program at SKB Palembang City. This type of research is development research with six stages consisting of collecting initial data , development product , expert validation , revision product , test try product analysis _ data . The research subjects consisted of one tutor and ten learning residents, and went through three stages of validation by three experts, namely linguists, materials experts, and media experts. The method of collection used questionnaires and interviews. The results of this data analysis show that this interactive Powerpoint learning media can be tested on the Palembang City SKB . small group trial with a total score of 371 with a percentage of 84.31%. This shows that the interactive Powerpoint learning media is feasible to be applied to learning in the SPNF SKB Palembang City, especially in the equality program.